Electrogenerated Chemiluminescence for Immunoassay Applications - Isnaini Rahmawati; Irkham Irkham; Rahmat Wibowo; Jarnuzi Gunlazuardi; Yasuaki Einaga; Tribidasari Anggraningrum Ivandini (Indonesian Journal of Chemistry, 2021)
Electrogenerated chemiluminescence (ECL) has recently become one of the most prominent and well-established transducers for immunoassay techniques. ECL relates a luminophore concentration in solution with the emission of light triggered by an electrochemical stimulus. ECL immunoassay (ECLIA) performance depends on the parameters of its light generation, including the luminophore, the species that emit light called labels in ECLIA; co-reactants, which are added reagents that support the luminophore to undergo the excited state; electrodes, which are the place for the ECL reactions to take place; and the format of the immunoassay. This review discusses the behaviour of ECLIA parameters, the required instrumentations, and some important examples of detections based on ECLIA.